PRODUCTIVITY OF PAKCOY (Brassica Rapa L.) WHICH CULTIVATED ORGANICALLY - Sri Rahayu; A. Tutik Purwani I (Jurnal Inovasi Penelitian, 2022)
This study aims to determine the interaction of chicken manure and Keong Mas liquid organic fertilizer (POC) on the growth and yield of pakcoy plants. This research was conducted on Jln. Palapa 3 A, Pontianak Selatan, from October to December 2020. This study used a factorial randomized block design with 3 (three) levels of treatment. Each treatment was repeated 3 (three) times and each replication consisted of 3 plant samples. The treatments are as follows: the first factor is chicken manure with code A consisting of 3 levels of treatment, namely: a1 = chicken manure with a dose of 40 grams / polybag, a2 = chicken manure with a dose of 60 grams / polybag, a3 = manure chicken with a dose of 80 grams / polybag. The second factor is the Keong Mas Liquid Organic Fertilizer (POC) with code K consisting of 3 treatment levels, namely: k1 = POC Keong Mas with a concentration of 0%, k2 = POC Keong Mas with a concentration of 2%, k3 = POC Keong Mas with a concentration of 4% . The variables observed in this study included: Plant Height (cm), Number of Leaves per Plant (strands), Amount of Chlorophyll (units) and Plant Fresh Weight (grams). The results showed that the interaction of chicken manure and POC Keong Mas had no significant effect on all the observed variables. Chicken manure had a very significant effect on plant height, amount of chlorophyll and plant fresh weight and had no significant effect on the number of leaves. Meanwhile, POC Keong Mas had a significant effect on plant height variables and had no significant effect on other observed variables